Relationship between Problem Solving and Assertiveness Skills among Nursing Students - Naiemeh Seyedfatemi; Zeinab Moshirabadi; Leili Borimnejad; Hamid Haghani (Tehran University of Medical Sciences, 2013)
Background & Aim: The nature of clinical practice has altered in recent years. It has been affected by different kinds of problem-solving modelschr('39') so, the problem-solving skill is necessary in practice for nurse practitioners. Besides assertiveness is a critical element which persuades nurses and nursing students to establish good relationships and use their knowledge and professional skills effectively. The aim of this study was to assess the relationship between problem solving and assertiveness skills among undergraduate nursing students .   Methods & Materials: This was a descriptive correlational study. The study was carried out in the School of Nursing and Midwifery at Iran University of Medical Sciences. The study population included all students enrolled in the four-year nursing program in 2009-2010. Data were collected using the Heppner and Petersen's problem solving inventory and Rathus assertiveness schedule. Data were analyzed using the ANOVA, independent sample t-test and Pearson Correlation Coefficient tests in the SPSS .    Results: Three hundred and twenty two students participated in this study. The studentschr('39') problem-solving skill (mean=89.5) and assertiveness (mean=12.1) were moderate. The study showed that last year students reported higher assertiveness skill than the freshmen (F=2.85 P≤0.037). The level of assertiveness was correlated with the level of problem-solving skill .   Conclusion: Educational programs should provide opportunities for nursing students to enhance life skills such as problem solving and assertiveness skills. Nursing schools should improve studentschr('39') skills in clinical approaches to be better care professional .